Effectiveness of the Use of Analgetic Drugs in Sectio Caesarea (SC) Patients at RSAL Mintoharjo - Atisi; Fajar Amirulah; Rizky Farmasita Budiastuti; Rangki Astiani (Jurnal FARMASIMED (JFM), 2026)
Cesarean section (CS) is a common obstetric surgical procedure that is frequently associated with moderate to severe postoperative pain, which may delay early mobilization and prolong recovery. This study aimed to evaluate the effectiveness of analgetic use based on the type and number of analgetics on pain intensity and recovery time in post-cesarean section patients at RSAL Mintoharjo. This research was conducted as an observational analytic study with a prospective cohort design involving 80 post-CS patients. Data were collected through medical records, direct observation, and pain assessment using the Numeric Rating Scale (NRS) at 6 hours, 24 hours and on day 2 or 3 postoperatively. Statistical analysis was performed using univariate analysis, Chi-Square test, and one-way ANOVA. The results show that the type of analgesic significantly affects pain intensity at all measurement times (p < 0,05), with combination analgetic regimens providing better pain control that single analgetics. The number of analgetics does not affect pain intensity at 6 hours postoperatively but shows a significant effect at 24 hours and during follow-up interviews. Recovery time is not significantly influenced by the type or number of analgesics, with most patients discharged within three days. Patient age and comorbidities affect pain intensity, while cesarean history and smoking status do not. In conclusion, multimodal analgesia is effective for controlling acute postoperative pain following cesarean section, whereas recovery time is more strongly influenced by patient clinical factors